2015
DOI: 10.1080/15592294.2015.1060389
|View full text |Cite
|
Sign up to set email alerts
|

Infant peripheral blood repetitive element hypomethylation associated with antiretroviral therapyin utero

Abstract: The use of combination antiretroviral therapy (cART) to prevent HIV mother-to-child transmission during pregnancy and delivery is generally considered safe. However, vigilant assessment of potential risks of these agents remains warranted. Epigenetic changes including DNA methylation are considered potential mechanisms linking the in utero environment with long-term health outcomes. Few studies have examined the epigenetic effects of prenatal exposure to pharmaceutical agents, including antiretroviral therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 60 publications
1
14
1
Order By: Relevance
“…31 Other mechanisms of toxicity, such as epigenetic effects and metabolic toxicities, may also play a role. 3840 While previous animal studies and case reports have noted potential associations of in utero efavirenz exposure with neural tube defects or other neurological outcomes, 3133 we observed only slightly elevated risk of neurological case (9.8% for EFV-exposed vs. 6.0% for EFV-unexposed) which did not attain statistical significance.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…31 Other mechanisms of toxicity, such as epigenetic effects and metabolic toxicities, may also play a role. 3840 While previous animal studies and case reports have noted potential associations of in utero efavirenz exposure with neural tube defects or other neurological outcomes, 3133 we observed only slightly elevated risk of neurological case (9.8% for EFV-exposed vs. 6.0% for EFV-unexposed) which did not attain statistical significance.…”
Section: Discussioncontrasting
confidence: 93%
“…However, we evaluated multiple domains of interest which could reflect mitochondrial dysfunction, epigenetic effects, or other mechanisms of toxicity related to intrauterine exposures. 3840 A potential limitation of our trigger-based approach is that it may have missed certain AEs, and all domains were treated equally which may not reflect the relative clinical significance of toxicities across different domains. In addition, ARV drugs could have opposing effects on different domains, which would tend to obscure associations with overall case status.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by previous studies that observed an accumulation of methylation in integrated viral genomes, in long-term-treated HIV patients 22 or a hipomethylating effect of atazanavir, a protease inhibitor, on AluYb8 repetitive element in infants exposed to ART in utero 26 .…”
Section: Discussionsupporting
confidence: 89%
“…Additional concepts enriched with an FDR of 10% include processes involved in viral processing and regulation, and this may be a result of treatment exposure or a response to viral exposure. The few previous studies examining the impact of HIV and maternal antiviral therapies on the neonatal epigenome suggest that antiviral treatment and not infection itself is the driver of change (50,51). Heterochromatin differences were observed in lymphocytes from children with prenatal nucleoside reverse transcriptase inhibitor (NRTI) exposure compared with children without NRTI exposure regardless of maternal HIV status (51).…”
Section: Discussionmentioning
confidence: 99%
“…Heterochromatin differences were observed in lymphocytes from children with prenatal nucleoside reverse transcriptase inhibitor (NRTI) exposure compared with children without NRTI exposure regardless of maternal HIV status (51). Likewise, maternal anti-viral therapy was associated with DNA hypomethylation at repetitive elements, a global marker, in newborn peripheral blood mononuclear cells (PBMCs) compared with newborns from untreated HIV-positive mothers (50). Of the eight HIV positive mothers in the MACE cohort, at the time of birth seven took Nevaripine (a non-NRTI), one additionally took azidothymidine (a NRTI), and one was untreated.…”
Section: Discussionmentioning
confidence: 99%